2017
DOI: 10.1523/eneuro.0387-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Dynamic Brain Activity Caused by Mild Traumatic Brain Injury Are Partially Rescued by the Cannabinoid Type-2 Receptor Inverse Agonist SMM-189

Abstract: Mild traumatic brain injury (mTBI) can cause severe long-term cognitive and emotional deficits, including impaired memory, depression, and persevering fear, but the neuropathological basis of these deficits is uncertain. As medial prefrontal cortex (mPFC) and hippocampus play important roles in memory and emotion, we used multi-site, multi-electrode recordings of oscillatory neuronal activity in local field potentials (LFPs) in awake, head-fixed mice to determine if the functioning of these regions was abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 108 publications
2
16
0
Order By: Relevance
“…Surprisingly, these effects were reversed with JWH133 treatment (a CB2R agonist) but exacerbated by AM630 treatment (a CB2R antagonist) (Sun et al, 2017). In animal models of traumatic brain injury (TBI), administration of a CB2R inverse agonist attenuated neuronal death in the cortex, striatum and amygdala (Bu et al, 2016), and reversed TBI-induced electrophysiological changes in hippocampal and prefrontal cortex oscillatory activity (Liu et al, 2017b). In a rat model of vascular dementia, the CB2R agonist BCP improved learning and memory on the Morris water maze, increased cerebral blood flow, and upregulated CB2R expression in the hippocampus (Lou et al, 2017).…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Surprisingly, these effects were reversed with JWH133 treatment (a CB2R agonist) but exacerbated by AM630 treatment (a CB2R antagonist) (Sun et al, 2017). In animal models of traumatic brain injury (TBI), administration of a CB2R inverse agonist attenuated neuronal death in the cortex, striatum and amygdala (Bu et al, 2016), and reversed TBI-induced electrophysiological changes in hippocampal and prefrontal cortex oscillatory activity (Liu et al, 2017b). In a rat model of vascular dementia, the CB2R agonist BCP improved learning and memory on the Morris water maze, increased cerebral blood flow, and upregulated CB2R expression in the hippocampus (Lou et al, 2017).…”
Section: Neuroinflammationmentioning
confidence: 99%
“…To control for the variability in subject sample and characteristics, animal models of TBI are a promising avenue to study the mechanisms of concussive injury from injury causation to changes to neural function, intracranial injury mechanisms, and histopathological changes post mortem. Research employing animal models of TBI combined with EEG measures have primarily used rats under lateral fluid percussion injury ( Biswas et al, 2018 ), projectile concussive impact ( Leung et al, 2014 ; Mountney et al, 2017 ), high deceleration impact system ( Napoli et al, 2012 ), a weight drop model ( Ucar et al, 2006 ), and mice under blast loading ( Liu et al, 2017 ) and also using the weight drop model ( Sabir et al, 2015 ). While differences observed in the power frequency bands between injured and non-injured animals were demonstrated, the measurement of EEG in these studies involved opening up the cranial vault and implanting electrodes directly on the brain.…”
Section: Translatable Metricsmentioning
confidence: 99%
“…In vivo animal studies showed that CB2R receptor is the main pharmacological target of natural or synthetic cannabinoids in protection against cognitive and motor impairment after TBI [ 1 , 44 , 45 , 46 , 47 , 48 , 49 , 51 , 54 , 55 , 57 , 58 , 59 , 60 ]. The inhibition of CB1R by SR141716 failed to show any beneficial effect on cognitive and motor impairment after TBI [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main mechanisms through which cannabinoids improve cognitive and motor impairment after TBI are associated with decreasing the pro-inflammatory markers [ 1 , 44 , 46 , 47 , 48 , 52 , 53 , 57 , 58 ], decreasing oedema formation [ 44 , 45 , 47 , 54 , 55 , 58 , 60 ], decreasing BBB permeability [ 44 , 45 , 46 , 54 , 55 , 57 ], preventing neuronal cell loss [ 44 , 49 , 51 , 55 ] and increasing the levels of adherens jonction proteins [ 45 , 46 , 54 ].…”
Section: Resultsmentioning
confidence: 99%